Caring for Images: Anonymization as Feminist Sensory Accompaniment - Ortiz, Arantxa (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
The expanding criminalization of political participation and dissent in the United States, especially in connection to non-citizens, warrants the use of creative experiments through which we can reorient how we apprehend, depict, and/or document marginalized groups. Drawing on my involvement in a campaign advanced by a Massachusetts immigrant rights collective and ethnographic research on the biometric industry, I interrogate how to creatively engage dilemmas of visibility and recognition experienced by illegalized groups engaged in dissenting practices. I examine the potential of AI-generated anonymization as a refusal of recognition politics. How might the use of computational anonymization disrupt how we apprehend images of the illegalized? In what ways can such anonymization techniques be complementary to anti-carceral imaginaries? And what kinds of compromises, if any, can we consent to when pursuing such “creative-critical” experiments in connection to surveilled and criminalized groups (Alvarez, Dattatreyan, and Shankar 2021)? This creative experiment, grounded on liberatory abolitionist commitments, argues for the productive potential of computational anonymization as a temporary and imperfect experiment in fugitivity and refusal. Conceived as a channel for sensory accompaniment, it aspires to motivate a shift in journalistic, ethnographic, and other documentation practices engaging the struggles of illegalized and otherwise criminalized groups.